PENULISAN SKENARIO DRAMA BERSETTING SEJARAH UNTUK OSIS SMP MUHAMMADIYAH SUMBANG BANYUMAS - Arifin Suryo Nugroho; Ipong Jazimah (Khazanah Pendidikan, 2019)
ABSTRACTThe problem discussed by partners is the limitations of students in terms ofunderstanding history and making drama scenarios, especially drama scenarioswith historical settings. This program aims to support creativity and students inreconstructing a historic event. Reconstruction then continued in making dramascenarios. Writing historical drama scenarios can provide alternative dramaperformances at school. Another benefit is fostering a sense of nationalism andnationality in students. The method used is training and mentoring. The resultsof this study are the increasing ability of students in making drama scenarioswith historical settings.Keywords: Student Council students, drama scenarios, historical understanding